Evaluation of the effect of the COVID-19 pandemic on the all-cause, cause-specific mortality, YLL, and life expectancy in the first 2 years in an Iranian population—an ecological study - Zahra Pirayesh; Seyed Mohammad Riahi; Ali Bidokhti; Toba Kazemi (Frontiers in Public Health, 2023)
BackgroundCOVID-19 pandemic resulted in excess mortality and changed the trends of causes of death worldwide. In this study, we investigate the all-cause and cause-specific deaths during the COVID-19 pandemic (2020–2022) compared to the baseline (2018–2020), considering age groups, gender, place of residence, and place of death in south Khorasan, east of Iran.MethodsThe present ecological study was conducted using South Khorasan Province death certificate data during 2018–2022. The number of death and all-cause and cause-specific mortality rates (per 100,000 people) were calculated and compared based on age groups, place of residence, place of death, and gender before (2018–2020) and during the COVID-19 pandemic (2020–2022). We also calculated total and cause-specific years of life lost (YLL) to death and gender-specific life expectancy at birth.ResultsA total of 7,766 deaths occurred from March 21, 2018, to March 20, 2020 (pre-pandemic) and 9,984 deaths from March 21, 2020, to March 20, 2022 (pandemic). The mean age at death increased by about 2 years during the COVID-19 pandemic. The mortality rate was significantly increased in the age groups 20 years and older. The most excess deaths were recorded in men, Aged more than 60 years, death at home, and the rural population. Mortality due to COVID-19 accounted for nearly 17% of deaths. The highest increase in mortality rate was observed due to endocrine and Cardiovascular diseases. Mortality rates due to the genitourinary system and Certain conditions originating in the perinatal period have decreased during the COVID-19 pandemic. The major causes of death during the pandemic were Cardiovascular diseases, COVID-19, cancer, chronic respiratory diseases, accidents, and endocrine diseases in both sexes, in rural and urban areas. Years of life lost (YLL) increased by nearly 15.0%, which was mostly due to COVID-19, life expectancy at birth has steadily declined from 2018 to202 for both genders (from 78.4 to 75).ConclusionIn this study, we found that All-cause mortality increased by 25.5% during the COVID-19 pandemic, especially in men, older adult, Rural residents, and those who died at home (outside the hospital). Considering that the most common causes of death during the COVID-19 pandemic are also non-communicable diseases. It is necessary to pay attention to non-communicable diseases even during the pandemic of a serious infectious disease like COVID-19. The years of life lost also increased during the COVID-19 pandemic, which is necessary to pay attention to all age groups, especially the causes of death in young people. In most developing countries, the first cause of death of these groups is accidents.